El presupuesto participativo entre democracia, pobreza y desarrollo (2007)
ABSTRACT: This article presents the results of the evaluative investigation done between 2005-2006 in Medellín (Colombia) about the 2005 participatory budget with the Corregimentales and Communal Consultative Councils (C.C.C.C). This was done through the consultation of diverse estates of the political, civil, and administrative society of the city, in accordance with the phases of management and the fulfillment of the program’s goals and objectives during this year, which facilitated making a balance about democratic governability and participation; planning and local development; and public management synthesized in three levels: the operative-functional, the methodological-normative and the political-strategic. The final discussion will deal with critical issues regarding participatory budgeting in terms of the transformations in the local power, the social woven and the erradication of poverty, retaking the approaches to other experiences of Latin America, and reports of the municipal administration and the veeduría of Medellín.